The Great Lockdown : lessons learned during the pandemic from organizations around the world - Das, Shivaji; Zutshi, Aroop; Janardhanan, Janesh; Frigstad, David B. (Hoboken, New Jersey : Wiley, 2022)
""The Great Lockdown" is an event not seen in the last 100 years. The implications for consumer behaviors and businesses are profound. Different countries and industries are feeling different degrees of impact from COVID-19. Many industries are seeing a net negative impact due to COVID-19 - tourism & leisure, aerospace, mobility, construction & real estate, and manufacturing. However, some other industries are seeing a net positive impact from COVID-19. Healthcare supplies, personal care, home care, ICT and digital collaboration, online learning, online gaming, eCommerce, catering are seeing demand spike during The Great Lockdown. Seen through the eyes of CEOs of billion-dollar corporations from across the world, this book chronicles the experience of various industries going into The Great Lockdown and navigating the crisis through initiatives impacting people, processes, and technology. It will highlight the 'hits' and the 'misses' and give leaders a strong sense of what to do within their own organizations should this happen again"--
A. Lange & Sohne -- Abacus Pharma -- Bangalore International Airport -- beCuriou -- Fonterra -- Globalization Partners -- GOGOX -- Hornet -- IndiGrid -- Julius Baer -- Realwear -- SAP -- SOS Children's Villages -- Tapsi -- Terumo -- Conclusion.
Includes index.
Keywords: COVID-19 Pandemic, 2020- -- Economic aspects; COVID-19 Pandemic, 2020- -- Social aspects; Quarantine -- Economic aspects -- 21st century; Economic history -- 21st century; Organizational change